Integrative Transcriptome and Proteome Analysis Reveals the Absorption and Metabolism of Selenium in Tea Plants [Camellia sinensis (L.) O. Kuntze] - Ren, Hengze; Li, Xiaoman; Guo, Lina; Wang, Lu; Hao, Xinyuan; Zeng, Jianming (Frontiers in Plant Science, 2022)
Certain tea plants (Camellia sinensis) have the ability to accumulate selenium. In plants, the predominant forms of bioavailable Se are selenite (SeO32-) and selenate (SeO42-). We applied transcriptomics and proteomics to hydroponically grown plants treated with selenite or selenate for 48 h in the attempt to elucidate the selenium absorption and assimilation mechanisms in tea. A total of 1,844 differentially expressed genes (DEGs) and 691 differentially expressed proteins (DEPs) were obtained by comparing the Na2SeO3 and Na2SeO4 treatments against the control. A GO analysis showed that the genes related to amino acid and protein metabolism and redox reaction were strongly upregulated in the plants under the Na2SeO3 treatment. A KEGG pathway analysis revealed that numerous genes involved in amino acid and glutathione metabolism were upregulated, genes and proteins associated with glutathione metabolism and ubiquinone and terpenoid-quinone biosynthesis were highly expressed. Genes participating in DNA and RNA metabolism were identified and proteins related to glutathione metabolism were detected in tea plants supplemented with Na2SeO4. ABC, nitrate and sugar transporter genes were differentially expressed in response to selenite and selenate. Phosphate transporter (PHT3;1a, PHT1;3b, PHT1;8) and aquaporin (NIP2;1) genes were upregulated in the presence of selenite. Sulfate transporter (SULTR1;1 and SULTR2;1) expression increased in response to selenate exposure. The results of the present study have clarified Se absorption and metabolism in tea plants.